Trip and personal characteristics towards the intention to cycle in Larnaca, Cyprus: an EFA-SEM approach - Nikolaou, Paraskevas; Basbas, Socrates; Politis, Ioannis; Borg, Georgios (My University, 2020)
Mobility is one of the most important and challenging aspects that influence climate change, air quality, and especially the quality of citizens’ lives. Therefore, creating sustainable transport solutions makes way for different modes of transport such as the bicycle, which is continuously gaining more supporters, due to the health, economic, and environmental benefits that it provides. However, cyclists are facing several barriers (e.g., lack of infrastructure), a fact that keeps away commuters from using a bicycle for their daily trips. Investigating the factors that reflect on the commuters’ intention to use a bicycle is a sine qua non for the promotion of sustainable mobility. Therefore, the objective of this paper is the investigation of the factors that prevent residents with low experience or with no cultural/lifestyle background in regards to cycling from cycling. The case study of the city of Larnaca (Cyprus) is deployed by exploring the socio-demographic and trip characteristics of the city’s residents and their relation with the intention to cycle. A two-step approach is developed, namely Explanatory Factor Analysis (EFA) and Structural Equation Modeling (SEM). Despite the promotion of cycling that education is attempting to do (successfully), other factors (such as age, distance, and time) appear to prevent Larnaca’s residents from cycling. Among the actions that local authorities should undertake is that of safety prevention of the vulnerable users of the road network. This group includes elderly people, who need major encouraging interventions by local policymakers and stakeholders
Keywords: exploratory factor analysis; structural equation modeling; intention; bicycle; sustainable mobility